Experimental and Numerical Simulation of Interlayer Propagation Path of Vertical Fractures in Shale - Xiong, Dong; Ma, Xinfang; Yang, Huanqiang; Liu, Yang; Zhang, Qingqing (Frontiers in Energy Research, 2021)
The complex fracture network formed by volume fracturing of shale gas reservoir is very important to the effect of reservoir reconstruction. The existence of bedding interface will change the propagation path of vertical fractures and affect the reservoir reconstruction range in the height direction. Therefore, it is of great significance to study the propagation path law of vertical fractures in shale reservoir. Firstly, the mechanical parameters of natural outcrop shale core are tested by three-point bending experiment, and the interlayer propagation path of vertical fractures is studied. Considering the difference between the experimental environment and the actual fracturing conditions of shale reservoir, based on the Cohesive element and considering the fluid-solid-damage coupling in the process of hydraulic fracturing, a two-dimensional numerical model of vertical fracture interlayer propagation is established. The interlayer propagation path of vertical fractures under different reservoir properties and construction parameters is calculated. According to the experimental results, the strength of bedding interface is the weakest, the crack propagation resistance along the bedding interface is the smallest, and the crack propagation path is straight; When the fracture is orthogonal or perpendicular to the bedding interface, the fracture propagation resistance is large, and the fracture appears arc propagation path or deflection. According to the numerical simulation results, the difference between vertical stress and minimum horizontal in-situ stress difference, interlayer in-situ stress difference and interface stiffness will have a significant impact on the propagation path of vertical fractures; Large displacement fluid injection and high viscosity fluid injection help vertical fractures pass through the bedding interface, and low viscosity fracturing fluid helps to open the bedding interface. This research work is helpful to better understand the characteristics of bedding shale and the interlayer propagation law of vertical fractures, and to form the stimulation strategy of shale gas reservoir.